Effects of Gestational Age, Birth Weight, and Hypoxemia on Pharmacokinetics of Amikacin in Serum of Infants - Myers, Martin G. (1977)
The serum pharmacokinetics of amikacin were studied in 36 infants treated for suspected bacterial infection. A prolonged serum half-life was associated with the related variables of birth at an early gestational age, low birth weight, and hypoxemia. A postnatal age effect was not apparent when hypoxemic infants were excluded.